2010
DOI: 10.1130/ges00580.1
|View full text |Cite
|
Sign up to set email alerts
|

Structural constraints on the timing of left-lateral shear along the Red River shear zone in the Ailao Shan and Diancang Shan Ranges, Yunnan, SW China

Abstract: The >1000-km-long Oligocene-Miocene left-lateral Red River shear zone (RRSZ) and metamorphic belt and the Pliocene-active right-lateral Red River fault (RRF), stretching from SE Tibet to the South China Sea, has been cited as one of the primary examples of a lithospheric scale strike-slip fault that has resulted in syn-kinematic metamorphism and partial melting and accommodated several hundred to a thousand kilometers of horizontal motion as a result of the indentation of India into Asia. Alternatively we inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
150
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 187 publications
(156 citation statements)
references
References 55 publications
(124 reference statements)
4
150
2
Order By: Relevance
“…A simple test of this theory would be that U-Pb monazite ages for peak metamorphism and magmatism would all have to date strike-slip motion along the faults. U-Pb monazite ages obtained from metamorphic rocks along the Karakoram Fault are Cretaceous (Streule et al 2009) and preliminary zircon ages from metamorphic rocks along the Red River Fault are Triassic in age (Searle et al 2010c), strongly suggesting that metamorphism was earlier than, and unconnected to shearing along the fault. Because the crust beneath western Tibet is up to 90 km thick (Wittlinger et al 2004;Rai et al 2006), these faults would have to penetrate these depths and remain coherent, an unlikely scenario given the high geothermal gradient and great depth.…”
Section: 'Rigid Block' Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…A simple test of this theory would be that U-Pb monazite ages for peak metamorphism and magmatism would all have to date strike-slip motion along the faults. U-Pb monazite ages obtained from metamorphic rocks along the Karakoram Fault are Cretaceous (Streule et al 2009) and preliminary zircon ages from metamorphic rocks along the Red River Fault are Triassic in age (Searle et al 2010c), strongly suggesting that metamorphism was earlier than, and unconnected to shearing along the fault. Because the crust beneath western Tibet is up to 90 km thick (Wittlinger et al 2004;Rai et al 2006), these faults would have to penetrate these depths and remain coherent, an unlikely scenario given the high geothermal gradient and great depth.…”
Section: 'Rigid Block' Modelsmentioning
confidence: 99%
“…This view suggests that the metamorphism and most of the granites were formed prior to strike-slip faulting and not by shear heating, and that the faults are purely crustal features where localized strain at the surface dissipates into a wide zone of distributed ductile shear at depth. This view has been promoted both for the Karakoram Fault in particular (Searle 1996;Searle et al 1998;Murphy et al 2000;Phillips et al 2004;Robinson 2009a,b) and for the Red River Fault Searle 2006Searle , 2007Yeh et al 2008;Searle et al 2010c).…”
mentioning
confidence: 99%
“…faults (Tapponnier et al, 1990;Leloup et al, 2007;Searle et al, 2010). Among these faults, the Ailaoshan has divided the Ailaoshan belt into two major lithotectonic successions ( Fig.…”
Section: Overviewmentioning
confidence: 99%
“…Mylonitized metamorphic rocks found in this shear zone exhibit structures which indicate left -lateral (sinistral) shearing, probably in relation to far -field collision of the Indian subcontinent with the Eurasian continent during the Eocene (e.g., Leloup et al, 1993). Furthermore, it has been suggested that the regional metamorphism in the Cangshan Mountains area was related to an earlier (Permo -Triassic) continental collision event involving the South China and Indochina cratons (e.g., Osanai et al, 2008;Searle et al, 2010). Metamorphic rocks of the Cangshan Mountains contain mineral assemblages that indicate greenschist facies to amphibolite facies metamorphic conditions.…”
Section: Cangshan Mountainsmentioning
confidence: 99%
“…Parts of the Red River Shear Zone experienced ultrahigh -temperature (UHT) conditions, as inferred from the coexistence of Grt, Crn, and Qtz in Kybearing Grt -Crn -Sil -Spl gneiss , 1998;Leloup et al, 2001;Gilley et al, 2003). Some older ages, between 220 and 265 Ma, have also been reported for rocks from this shear zone (e.g., Carter et al, 2001;Gilley et al, 2003), possibly related to older continental collision event, as suggested by Osanai et al (2008) and Searle et al (2010).The metamorphosed mafic rocks of the Red River Shear Zone analyzed in this study were collected from the Song Hong and Xuan Dai groups (Fig. 2).…”
mentioning
confidence: 99%